2019
DOI: 10.3390/brainsci9040077
|View full text |Cite
|
Sign up to set email alerts
|

The Modulating Role of Self-Referential Stimuli and Processes in the Effect of Stress and Negative Emotion on Inhibition Processes in Borderline Personality Disorder: Proposition of a Model to Integrate the Self-Concept and Inhibition Processes

Abstract: Impulsivity is an important clinical and diagnostic feature of borderline personality disorder (BPD). Even though it has been reported that BPD individuals’ inhibition performance is significantly reduced in the context of negative emotion or stress, this literature shows mixed results, raising questions about the possible role played by other factors. Winter (2016) proposed that negative emotion stimuli can be more disruptive for BPD individuals’ attention control performance because they induce higher distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(180 reference statements)
1
2
0
Order By: Relevance
“…From the results obtained, it is possible to formulate new hypotheses that could be investigated in future experiments. First, the results of the present study clarify the links that were expected in Gagnon and collaborators’ model [28] between splitting and RPI by suggesting that those relationships cannot be seen in the same way for positive and negative object relations. Furthermore, by clarifying the relationships between splitting and the PI index with negative words, it is possible to propose some hypotheses regarding the neurobiological correlates of splitting.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…From the results obtained, it is possible to formulate new hypotheses that could be investigated in future experiments. First, the results of the present study clarify the links that were expected in Gagnon and collaborators’ model [28] between splitting and RPI by suggesting that those relationships cannot be seen in the same way for positive and negative object relations. Furthermore, by clarifying the relationships between splitting and the PI index with negative words, it is possible to propose some hypotheses regarding the neurobiological correlates of splitting.…”
Section: Discussionsupporting
confidence: 82%
“…In general, studies of inhibition processes have reported that inhibition performance among BPD individuals is significantly reduced, especially when presented with negative emotional stimuli or self-referential material that contains themes specific to BPD, such as abandonment [28]. To explain the particular effect of emotional stimuli on the three inhibition processes of BPD individuals, Gagnon and colleagues [28] proposed a model adapted from certain propositions of Kernberg's theory. Here, the BPD self-concept belongs to long-term memory and is composed of split representations of self and other that will likely produce intense emotional responses and consequently disrupt the process of resistance to distractor interference and prepotent Psychopathology 2022;55:345-361 DOI: 10.1159/000525006 response inhibition.…”
Section: Inhibition Functions and Splittingmentioning
confidence: 99%
See 1 more Smart Citation